The Dead Sea scrolls and the New Testament - Cook, Johann (Old Testament essays, 1993)
It is the aim of this article to review a recent republished collection of articles in which the authors all endeavour to put into perspective the Semitic (Jewish) background of the New Testament. In some respects the collection seems to be modem and up to date. In others, however, it is dated and has specific shortcomings, mainly being of too limited scope. The past thirty-five years of Dead Sea Scrolls research has indeed advanced the knowledge of their historical background and the scientific understanding of these texts. In the main the different contributions opened perspectives which are still valid today.